Installation of LYRM proteins in early eukaryotes to regulate the metabolic capacity of the emerging mitochondrion - Dohnálek, Vít; Doležal, Pavel (Open biology, 2024)
Core mitochondrial processes such as the electron transport chain, protein translation and the formation of Fe-S clusters (ISC) are of prokaryotic origin and were present in the bacterial ancestor of mitochondria. In animal and fungal models, a family of small Leu-Tyr-Arg motif-containing proteins (LYRMs) uniformly regulates the function of mitochondrial complexes involved in these processes. The action of LYRMs is contingent upon their binding to the acylated form of acyl carrier protein (ACP). This study demonstrates that LYRMs are structurally and evolutionarily related proteins characterized by a core triplet of α-helices. Their widespread distribution across eukaryotes suggests that 12 specialized LYRMs were likely present in the last eukaryotic common ancestor to regulate the assembly and folding of the subunits that are conserved in bacteria but that lack LYRM homologues. The secondary reduction of mitochondria to anoxic environments has rendered the function of LYRMs and their interaction with acylated ACP dispensable. Consequently, these findings strongly suggest that early eukaryotes installed LYRMs in aerobic mitochondria as orchestrated switches, essential for regulating core metabolism and ATP production.
Keywords: molekulární evoluce; fylogeneze; LECA; lidé; sekvence aminokyselin; mitochondrial evolution; Humans; protein přenášející acyl; Animals; acyl-ACP; molekulární modely; Acyl Carrier Protein; zvířata; mitochondrie; mitochondriální proteiny; Phylogeny; Mitochondria; LYRM proteins; Mitochondrial Proteins; Eukaryota; Amino Acid Sequence; Evolution, Molecular; Models, Molecular